Reserves for Power Consumption Decrease in Gas Cleaning and Ventilation Systems - V. V. Kuzmin; D. I. Misioulia; V. A. Markov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper analyzes reasons of energy losses at various sections of gas-cleaning and ventilation systems: gas-cleaning equipment, flues, draft system. Non-used or less common technical and organizational power saving methods of this sphere are considered in the paper. The paper reveals possible directions for usage of economic mechanisms with the purpose to increase efficiency of power resource usage.